An analysis of Charles Dickens's gender-based use of speech verbs. (29th December 2016) - Ruano, Pablo
Abstract : This article presents a study of Charles Dickens's gender-based use of speech verbs. The aim of the analysis is to demonstrate that gender is one dimension of variation in the way in which Dickens constructs characters through their ways of speaking, thereby reinforcing the well-established antagonistic representation of male and female character types in his fictional universe. The article focuses on the 130 verbs identified in his fourteen complete novels, more than half of which (73) are associated exclusively, or almost exclusively, with either male or female figures. As will be shown, the systematic use of these gender-marked verbs reveals different personality traits that trigger information about both genders, thus contributing to their dichotomous characterisation. The analysis will also shed further light upon the dominant Victorian ideology concerning the representation of gender in fiction.